2005
DOI: 10.1016/j.ijheatmasstransfer.2004.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Conduction and entrance effects on laminar liquid flow and heat transfer in rectangular microchannels

Abstract: The paper presents both three and two-dimensional numerical analysis of convective heat transfer in microchannels. The three-dimensional geometry of the microchannel heat sink followed the details of the experimental facility used during a previous research step. The heat sink consisted of a very high aspect ratio rectangular microchannel. Two channel spacings, namely 1 mm and 0.3 mm (0.1 mm), were used for three-dimensional (two-dimensional) numerical model, respectively. Water was employed as the cooling liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
83
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(89 citation statements)
references
References 25 publications
(42 reference statements)
4
83
2
Order By: Relevance
“…Gamrat et al [42] studied conduction and entrance effects in rectangular microchannels both experimentally and numerically, with a 3D conjugate heat transfer model, Reynolds numbers in the range 200-3000, d h between 0.2 and 2 mm, and using water as the test fluid. They observed a significant reduction in the measured Nu when the hydraulic diameter was below 1 mm.…”
Section: Conjugate Heat Transfermentioning
confidence: 99%
See 2 more Smart Citations
“…Gamrat et al [42] studied conduction and entrance effects in rectangular microchannels both experimentally and numerically, with a 3D conjugate heat transfer model, Reynolds numbers in the range 200-3000, d h between 0.2 and 2 mm, and using water as the test fluid. They observed a significant reduction in the measured Nu when the hydraulic diameter was below 1 mm.…”
Section: Conjugate Heat Transfermentioning
confidence: 99%
“…Another investigation into flow and heat transfer through an individual circular microchannel The experimental apparatus of Gao et al [20] was considered in the papers of Gamrat et al [42] and Bavière et al [59]. Gamrat et al [42] performed detailed numerical analysis of the experimental system, modelling its 3D geometry and accounting for entrance effects and 3D conjugate heat transfer in the fluid and the solid walls.…”
Section: Measurement Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of experimental studies [1,2,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], besides theoretical [22][23][24] and numerical studies [5,[25][26][27][28], have been carried out, in the past decades, seeking to investigate the hydrodynamics and heat transfer characteristics in microscale. The results obtained in several of these studies show diversions among themselves and, also, with the conventional theory.…”
Section: Introductionmentioning
confidence: 99%
“…Some numerical studies [45,46] showed that the Nusselt number is more sensitive to the shape of the cross-section of the microchannels in comparison to other parameters, such as surface roughness, for example. Furthermore, there are numerical and theoretical studies that consider simplifications which differ a lot from what actually should occur experimentally as, for example, the negligence of viscous dissipation in numerical model [28,47], the true boundary condition at the limits [44] and the consideration of the fluid with constant thermophysical properties, in general.…”
Section: Introductionmentioning
confidence: 99%